2016
DOI: 10.1016/j.chom.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Consequences of Intestinal Fungal Dysbiosis

Abstract: Compared to bacteria, the role of fungi within the intestinal microbiota is poorly understood. In this study we investigated whether the presence of a “healthy” fungal community in the gut is important for modulating immune function. Prolonged oral treatment of mice with antifungal drugs resulted in increased disease severity in acute and chronic models of colitis, and also exacerbated the development of allergic airway disease. Microbiota profiling revealed restructuring of fungal and bacterial communities. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
354
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(387 citation statements)
references
References 38 publications
(48 reference statements)
10
354
2
5
Order By: Relevance
“…However, more recent clinical studies examining fecal loads have demonstrated increased Candida levels with antibotic treatment (101). Overgrowth may facilitate localized mucosal infection and/or generalized GI tract disturbances, but the validity of GI candidiasis via overgrowth as a clinical entity is controversial (102,103). This has been difficult to verify due to the lack of specific symptoms (belching, bloating, indigestion, nausea, diarrhea, and gas) and lack of diagnostic tests.…”
Section: Non-cd4mentioning
confidence: 99%
“…However, more recent clinical studies examining fecal loads have demonstrated increased Candida levels with antibotic treatment (101). Overgrowth may facilitate localized mucosal infection and/or generalized GI tract disturbances, but the validity of GI candidiasis via overgrowth as a clinical entity is controversial (102,103). This has been difficult to verify due to the lack of specific symptoms (belching, bloating, indigestion, nausea, diarrhea, and gas) and lack of diagnostic tests.…”
Section: Non-cd4mentioning
confidence: 99%
“…In a house dust mite-induced airway allergy model, disruption of the gut fungal community with antifungal drugs increased disease severity (181). Aspergillus amstelodami, Epicoccum nigrum, and Wallemia sebi increased in abundance during antifungal drug-induced fungal dysbiosis, and intestinal supplementation with these strains replicated the detrimental effects of antifungal drugs on lung allergy (181).…”
Section: Antifungal Immunity and The Study Of The Mycobiomementioning
confidence: 99%
“…Fungi are present in the mammalian intestine (15), yet little is known about their ability to influence immune homeostasis. The recent advances in deep sequencing technologies have redefined our understanding of the fungal communities (mycobiota) colonizing the mammalian barrier surfaces(2).…”
mentioning
confidence: 99%